Synchrotron tests of 3D Medipix2 and TimePix X-Ray Detectors - Mac Raighne, A; Akiba, K; Alianelli, L; Artuso, M; Bates, R; Bayer, F; Buytaert, J; Collins, P; Crossley, M; Eklund, L; Fleta, C; Gallas, A; et al. (2009)
In this article we report on the use micro-focus synchrotron X-ray radiation and pion beams to compare the detection efficiencies and charge sharing properties of novel 3D detectors to that of the current planar technology. Detector substrates are bump-bonded to the Medipx2 and Timepix chips. 55μm square pixel maps of the detection efficiencies have been produced using X-ray and MIP beams. For X-rays, a drop of 3-4% detection efficiency over the pixel area was found due to the central electrode. The corner electrodes show no degradation in efficiency compared to that of the planar device. For MIPs a drop of 0.5% in efficiency due to the central electrode was observed. Evidence of a considerable reduction in charge sharing in the 3D detectors compared to the planar devices is also shown. ©2009 IEEE.